Family functioning in families with a child with Down syndrome: A mixed methods approach - Povee, Kate; Roberts, Lynne; Bourke, J.; Leonard, H. (Wiley-Blackwell Publishing Ltd, 2012)
Background: This study aimed to explore the factors that predict functioning in families with a child with Down syndrome using a mixed methods design. The quantitative component examined the effect of maladaptive and autism-spectrum behaviours on the functioning of the family while the qualitative component explored the impact of having a child with Down syndrome on family holidays, family activities and general family functioning. Methods: Participants in this study were 224 primary caregivers of children with Down syndrome aged 4–25 years (57.1% male; 42.9% female) currently residing in Western Australia (74.0% in metropolitan Perth and 26.0% in rural Western Australia). Results: Maladaptive and autism-spectrum behaviour were associated with poorer family functioning. Mean total scores on the measures of family functioning and marital adjustment were comparable to that of families of typically developing children. Consistent with the quantitative findings, normality was the most common theme to emerge in the qualitative data. Child problem behaviours were also identified by parents/carers as having a negative impact on the family. Conclusions: This study has implications for the development of programs to support families with a child with Down syndrome and may dispel some of the myths surrounding the impact of intellectual disability on the family.